2021
DOI: 10.1002/ece3.8005
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects of a rapidly spreading native alga on a key herbivore

Abstract: Multiple anthropogenic stressors are causing a global decline in foundation species, including macrophytes, often resulting in the expansion of functionally different, more stressor‐tolerant macrophytes. Previously subdominant species may experience further positive demographic feedback if they are exposed to weaker plant–herbivore interactions, possibly via decreased palatability or being structurally different from the species they are replacing. However, the consequences of the spread of opportunistic macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…In marine communities, the preference and performance of the herbivores often relate directly to the nutritional value of algae or some other autotrophs, which is driven mostly by the protein and nitrogen content [ 151 , 152 , 153 , 154 , 155 ]. For example, several studies on the high-value marine abalone (Haliotis asinine) suggested that their diverse preferences are primarily influenced by the protein and nitrogen content of macroalgae [ 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 ]. Table 3 shows some examples of studies involving the interactions between marine autotrophs and herbivores based on the herbivore nutrient acquisition since the 2010s.…”
Section: Does Nutrient Acquisition In Algae Determine the Feeding Pre...mentioning
confidence: 99%
See 2 more Smart Citations
“…In marine communities, the preference and performance of the herbivores often relate directly to the nutritional value of algae or some other autotrophs, which is driven mostly by the protein and nitrogen content [ 151 , 152 , 153 , 154 , 155 ]. For example, several studies on the high-value marine abalone (Haliotis asinine) suggested that their diverse preferences are primarily influenced by the protein and nitrogen content of macroalgae [ 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 ]. Table 3 shows some examples of studies involving the interactions between marine autotrophs and herbivores based on the herbivore nutrient acquisition since the 2010s.…”
Section: Does Nutrient Acquisition In Algae Determine the Feeding Pre...mentioning
confidence: 99%
“…The lack of preference for protein-enriched algae (i.e., high-nutrient algae) can be explained by the compensatory feeding behaviour of some herbivore species. Previous studies reported the optimal growth rate and adequate intakes of limiting nutrients by testing the consumption rates of different herbivores on the low nutritional quality of algae foods [ 39 , 43 , 164 , 165 ]. According to Bradley et al (2021), herbivores may avoid species that are less palatable or have lower nutritional value, which may affect their distribution and abundance [ 164 ].…”
Section: Does Nutrient Acquisition In Algae Determine the Feeding Pre...mentioning
confidence: 99%
See 1 more Smart Citation